1189 ASSESSMENT OF DISCHARGE DESTINATION FOLLOWING SHORT-TERM DELIRIUM PLACEMENT. (16th January 2023) - Morrison, E; Muthukrishnan, V
Abstract: Introduction: "Pathway three delirium" is a short-term placement in a care home specific to North Yorkshire, for patients diagnosed with delirium during hospital admission, who are medically fit but have not recovered cognitively enough for discharge home. The goal is to allow extra time to recover from delirium, to allow return to patients' own homes. At this placement, patients are followed up by the acute hospital liaison team. Aims: To assess final discharge destinations after pathway three delirium placement. To analyse characteristics between discharge groups. Methods: We analysed electronic records of patients on this pathway between August 2020 and November 2021. Data was gathered on age, gender, prior cognitive impairment, visual impairment, hearing impairment, living alone, requiring package of care, and alcohol misuse. Results: 64 patients were included, 39 females (61%), 25 males (39%), average age of 83.7 years. 20 (31%) were discharged home, 26 (41%) remained in residential or nursing homes, 10 (16%) were readmitted to hospital, 8 (12%) discharge location was unknown or "other". Average age of those discharged home was 82.65yo, those discharged to residential/nursing homes: 83.88yo, and those readmitted: 85.8yo. 80% of those discharged home were women, compared to 61% of the total group and 50% of those who remained in nursing/residential care. The discharged home group contained 80% patients who lived alone, versus 58% in the residential/nursing home group, and 30% in readmitted. 25% of the home group had a care package pre-admission: versus 46% in the residential/nursing home group, and 38% across all groups. Cognitive impairment, sensory impairment and alcohol intake showed no apparent difference across destination. Conclusions: These findings show that this short-term delirium placement enables some patients to return to their own home. Analysis suggests that younger patients, women and those with apparently less social support were more likely to go home.